PENGARUH FASILITAS, KEPUASAN DAN KEPERCAYAAN TERHADAP LOYALITAS NASABAH MOBILE BANKING BANK JATENG CABANG UTAMA SEMARANG - Nurhidayah, Evinta Amalia; Ernawati, Fidyah Yuli; Irmawati, Monica (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
Abstract. Mobile banking (m-banking) has a big role in increasing customer loyalty. Easy access via smartphone devices, m-banking allows users to manage their finances without having to visit the bank physically. With this convenience, it builds a positive experience, which ultimately increases customer loyalty to the banking services provided. To find out whether the variables of facilities, satisfaction, and trust affect the loyalty of Bank Jateng Semarang Main Branch mobile banking customers. The population in this study is Bank Jateng Semarang City customers and the sample used in this study is 72 customers. The sampling technique in this study uses non-probability sampling with accidental sampling technique.The analytical tools in this study include instrument tests (validity test, reliability test), classical assumption test (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression, hypothesis test through t-test, F test, and determination coefficient test. The results of this study prove that the facility variable (X1) on customer loyalty has a t-value of 2.522 > t table 1.994 and a significance value of 0.014 < 0.05. The variable of satisfaction (X2) for customer loyalty has a t-value of 5.095 > t table 1.994 and a significance value of 0.000 < 0.05. The trust variable (X3) for customer loyalty has a t-value of 2.617 > t table 1.994 and a significance value of 0.011 < 0.05. Based on the results of the f test (model feasibility), the F value was calculated as 83.788 > F table (3.13) with a significant level of 0.000 < 0.05, which shows that the variables of facilities, satisfaction, and trust are variables that are worthy of being used as a research model. The value of the determination coefficient (Adjusted R Square) was obtained at 0.778 which means that 77.8% of customer loyalty can be explained by the variables of facilities, satisfaction and trust. While the rest is influenced by several other factors that are not available in this study. The conclusion of this study is that facilities have a positive and significant effect on customer loyalty in mobile banking Bank Jateng Semarang Main Branch. Satisfaction has a positive and significant effect on customer loyalty at Bank Jateng Mobile Banking Semarang Main Branch. Trust has a positive and significant effect on customer loyalty in mobile banking Bank Jateng Semarang Main Branch. Suggestions from the results obtained by Bank Jateng researchers suggest improving the quality of mobile banking services through innovative, safe, easy-touse features, customer support services, digital education and loyalty programs to increase customer trust and satisfaction.